Abundance and Distribution of Millipedes (Diplopoda) in Wera Nature Recreation Park - Rifana Lemba; Syech Zainal; Rafiqa Rafiqa; Fatmah Dhafir; Masrianih Masrianih; Manap Trianto (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Millipedes (Diplopoda) play an important role in forest ecosystems, particularly in the decomposition of organic matter and the recycling of nutrients, thereby contributing to soil fertility and ecosystem stability. This study aimed to determine the abundance and distribution patterns of millipedes (Diplopoda) in Wera Nature Recreation Park, Balumpewa Village, West Dolo District, Sigi Regency, Central Sulawesi. The research was designed as a quantitative descriptive study. Sampling was carried out using an exploratory survey method combined with hand collection techniques at three observation stations. These stations were selected using purposive sampling based on differences in environmental characteristics and habitat conditions. Data collection was conducted in three repetitions at two-week intervals to obtain representative data on millipede communities. In addition to species collection, measurements of physical environmental parameters were also performed, including light intensity, soil pH, air temperature, and humidity, as these factors are known to influence the presence and distribution of soil macrofauna. The results showed that six millipede species were recorded, belonging to three orders and three families. The average environmental conditions at the study site included a light intensity of 722.2 lux, soil pH of 6.8, temperature of 28.2°C, and humidity of 76.7%. These conditions indicate a habitat that is relatively less optimal for millipede populations. The species abundance index was classified as low, suggesting limited population sizes within the study area. However, the Relative Abundance Index (RAI) revealed variation among species, with two species categorized as having high relative abundance, one species moderate, and three species low. Analysis using Morisita’s Index and the Standardized Morisita Index (Ip) demonstrated that all recorded species exhibited a clumped distribution pattern. This distribution suggests that millipedes tend to concentrate in specific microhabitats that provide suitable moisture, shelter, and food resources. Overall, the findings indicate that unstable environmental conditions may restrict millipede distribution, causing them to utilize only particular microhabitats that meet their ecological requirements.